2017
DOI: 10.1016/j.molmet.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue (BAT) specific vaspin expression is increased after obesogenic diets and cold exposure and linked to acute changes in DNA-methylation

Abstract: ObjectiveSeveral studies have demonstrated anti-diabetic and anti-obesogenic properties of visceral adipose tissue-derived serine protease inhibitor (vaspin) and so evoked its potential use for treatment of obesity-related diseases. The aim of the study was to unravel physiological regulators of vaspin expression and secretion with a particular focus on its role in brown adipose tissue (BAT) biology.MethodsWe analyzed the effects of obesogenic diets and cold exposure on vaspin expression in liver and white and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 70 publications
3
33
0
1
Order By: Relevance
“…The expression pattern of mouse vaspin mRNA was more similar to that of human vaspin mRNA [4,5]. Furthermore, our result supports the earlier result for mouse vaspin [6]. We have demonstrated that the expression of hepatic vaspin was markedly decreased in liverspecific C/EBPα knockout mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The expression pattern of mouse vaspin mRNA was more similar to that of human vaspin mRNA [4,5]. Furthermore, our result supports the earlier result for mouse vaspin [6]. We have demonstrated that the expression of hepatic vaspin was markedly decreased in liverspecific C/EBPα knockout mice.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, vaspin mRNA level was higher in OLETF rats than in non-diabetic control rats [1]. Further, vaspin expression was observed in humans [4,5] or mice [6] in several tissues such as adipose tissue, liver, skeletal muscle, pancreas, and skin, with the highest production being observed in the liver or skin.…”
Section: Visceral Adipose Tissue-derived Serine Protease Inhibitor (Vmentioning
confidence: 90%
“…Seven studies [8][9][10][11][12][13][14] were selected after all the eligibility criteria were met (Table I). Regarding the location in which the studies were carried out, two were from Japan, and the others were from Spain, the United States of America, Sweden, Germany, and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Another study suggests that DNA methylation is involved in the brown adipocyte-specific expression of Vaspin (visceral adipose tissue-derived serine protease inhibitor; SERPINA12). Vaspin is an adipokine suggested to be anti-diabetic and antiobesogenic [48] because it inhibits hepatic gluconeogenesis and improves insulin signal transduction [49][50][51]. A microarray study found that Vaspin level is strongly upregulated in BAT after cold exposure, and another study found that Vaspin promoter regions in BAT are more hypomethylated than white adipose depots in mice fed with normal chow.…”
Section: Dna Methylation In Brown Adipocyte Gene Regulationmentioning
confidence: 99%